The Role of L-Sorbose Metabolism in Enhancing Fitness and Virulence in Escherichia coli Under Acidic Conditions - Qiu T; Chen X; Deng X; Zhang G; Wen S; Wu J; Sun D; Li T; Yan B; Dai M; Zhong LL; Tian GB (Infection and Drug Resistance)
Tian Qiu,1,* Xudong Chen,1,* Xue Deng,2– 5 Guili Zhang,2– 5 Shu’an Wen,2– 5 Ji Wu,2– 5 Dandan Sun,6 Tong Li,2– 5 Bin Yan,2,7 Min Dai,1 Lan-Lan Zhong,2– 5 Guo-Bao Tian2– 5 1School of Laboratory Medicine, Chengdu Medical College, Chengdu, 610500, People’s Republic of China; 2Advanced Medical Technology Center, The First Affiliated Hospital, Zhongshan School of Medicine, Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China; 3State Key Laboratory of Oncology in South China, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 4Department of Immunology, School of Medicine, Sun Yat-Sen University, Shenzhen, 518107, People’s Republic of China; 5Key Laboratory of Tropical Diseases Control (Sun Yat-Sen University), Ministry of Education, Guangzhou, 510080, People’s Republic of China; 6School of Medicine, Xizang Minzu University, Xianyang, 712082, People’s Republic of China; 7Department of Neonatal Surgery, Guangzhou Women and Children’s Medical Center, Guangzhou, 510080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guo-Bao Tian, Department of Immunology, School of Medicine, Sun Yat-Sen University, Shenzhen, 518107, People’s Republic of China, Tel/Fax +86 20 87335387, Email tiangb@mail.sysu.edu.cn Lan-Lan Zhong, Department of Immunology, School of Medicine, Sun Yat-Sen University, Shenzhen, 518107, People’s Republic of China, Tel/Fax +86 20 87335387, Email lanlanzhong74@163.comBackground: Pathogenic Escherichia coli (E. coli) causes a wide range of infections in humans and animals, imposing a significant global health burden. While metabolic flexibility is critical for E. coli fitness to host environments, the role of secondary carbon sources like L-Sorbose remains poorly characterized.Methods: The functional importance of L-Sorbose metabolism in E. coli CFT073 was investigated under acidic conditions simulating gastrointestinal and urinary tract environments. A ΔsorD mutant, with deletion of a key gene in L-Sorbose catabolism, was generated, and its growth, viability, virulence factors, proton motive force (PMF), oxidative stress levels, and transcriptomic profiles under acidic pH (3.5– 5.5) were assessed. Virulence was further tested using a Galleria mellonella infection model.Results: Deletion of sorD caused severe growth defects, loss of virulence factors (flagella and fimbriae), disrupted PMF, and oxidative stress accumulation under acidic conditions. Transcriptomic analysis revealed dysregulation of energy metabolism pathways and downregulation of virulence-associated genes in the ΔsorD mutant. Importantly, L-Sorbose metabolism deficiency significantly attenuated bacterial survival at pH 3.5 and reduced virulence in the G. mellonella model.Conclusion: These findings demonstrate that L-Sorbose metabolism is essential for E. coli to maintain energy homeostasis, virulence, and acid resistance. Targeting this pathway may offer a novel therapeutic strategy against pathogenic E. coli infections.Keywords: pathogenic Escherichia coli, virulence, fitness, L-Sorbose metabolism, acid tolerance, oxidative stress